Statistical analysis and evaluation of the depth of the ruts on Lithuanian state significance roads - Erinijus Getautis; Henrikas Sivilevičius (Mokslas: Lietuvos Ateitis, 2011)
The paper aims to determine the statistical indicators of distribution of the calculated rut depth of the state significance roads and to check their compliance with the requirements raised. The analysis of the works, investigating the problems of rut development and deepening on asphalt pavement and their effect on traffic conditions, is presented. The models of the dynamics of rut development on asphalt road pavement are also given. The experimental research aimed at determining the distribution of rut depth on the state significance highway Vilnius–Kaunas is described. The conclusions made are also presented.